2005
DOI: 10.1074/jbc.m413275200
|View full text |Cite
|
Sign up to set email alerts
|

A Causative Role of Stromelysin-3 in Extracellular Matrix Remodeling and Epithelial Apoptosis during Intestinal Metamorphosis in Xenopus laevis

Abstract: The matrix metalloproteinases are a family of proteases capable of degrading various components of the extracellular matrix. Expression studies have implicated the involvement of the matrix metalloproteinase stromelysin-3 (ST3) in tissue remodeling and pathogenesis. However, the in vivo role of ST3 has been difficult to study because of a lack of good animal models. Here we used intestinal remodeling during thyroid hormone-dependent metamorphosis of Xenopus laevis as a model to investigate in vivo the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 63 publications
6
64
0
1
Order By: Relevance
“…Next, to determine ST3 function in vivo, we used transgenic Xenopus tadpoles that express ST3 under a heat shock-inducible promoter (Fu et al, 2005). Overexpression of ST3 induced the larval epithelial apoptosis even in the absence of TH.…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…Next, to determine ST3 function in vivo, we used transgenic Xenopus tadpoles that express ST3 under a heat shock-inducible promoter (Fu et al, 2005). Overexpression of ST3 induced the larval epithelial apoptosis even in the absence of TH.…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…Another approach involves the heat-shock promoter (Wheeler et al, 2000) to drive expression of the recombinase and has already been applied in transgenic zebrafish (Thummel et al, 2005). As the heat-shock promoter has been used most successfully for conditional transgenesis in Xenopus without showing any basal activity (Buchholz et al, 2004;Fu et al, 2005), a heat-shock promoter-controlled Cre strain would be the most promising approach to ubiquitously activate silent reporter genes in transgenic reporter strains. Importantly, both conditional systems will allow a defined activation of the recombinase at any time of Xenopus development.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic animals and their wild type siblings were obtained by mating parental lines generated as previously described, and the transgenic animals were identified by the expression of GFP in the lens of their eyes (33). Wild type and transgenic tadpoles were heat-shocked twice at 34°C for 30 min, separated by 30 min at 18°C (33,53).…”
Section: Methodsmentioning
confidence: 99%
“…Microscopic and histochemical analyses have shown that at least the muscle and epidermal cells undergo T3-dependent apoptosis during metamorphosis (23,29,51,52). To study whether ST3 regulates apoptosis of these two cell types, we have made use of the transgenic animals that express a transgenic ST3 under the control of a heat shock-inducible promoter (33). We show that whereas extensive apoptosis is present in both the epidermis and muscles during natural as well as T3-induced metamorphosis, transgenic expression of ST3 induces cell death predominantly in the muscles.…”
mentioning
confidence: 99%
See 1 more Smart Citation